2014
DOI: 10.18052/www.scipress.com/ilshs.35.1
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Human Capital Development in Nigeria through the Lens of Education

Abstract: The paper assesses human capital development in Nigeria through the lens of education. The study used education as proxy to capture human capital, while utilizing secondary sources of data. There is evidence that human capital development in Nigeria is inadequate and unable to galvanise the economy towards long-term stable growth. Emphasis should be placed on deliberately developing the country's vast human resources, with particular reference to the country's educational spectrum, if the goal of poverty allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…This largely affects the ability of Universities in Nigeria to compete favourably with others around the world, as evident in the various university rankings done around the world based on various criteria. According to Martins & Olarinde (2014), 8 of the top 10 ranking universities in the world were in the United States of America in 2008, while no Nigerian university ranked among the first 6000. Similarly, Martins & Olarinde (2014) indicated that of the top 100 African universities in the 2011 ranking, the best university in Nigeria was placed in the 30th position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This largely affects the ability of Universities in Nigeria to compete favourably with others around the world, as evident in the various university rankings done around the world based on various criteria. According to Martins & Olarinde (2014), 8 of the top 10 ranking universities in the world were in the United States of America in 2008, while no Nigerian university ranked among the first 6000. Similarly, Martins & Olarinde (2014) indicated that of the top 100 African universities in the 2011 ranking, the best university in Nigeria was placed in the 30th position.…”
Section: Introductionmentioning
confidence: 99%
“…According to Martins & Olarinde (2014), 8 of the top 10 ranking universities in the world were in the United States of America in 2008, while no Nigerian university ranked among the first 6000. Similarly, Martins & Olarinde (2014) indicated that of the top 100 African universities in the 2011 ranking, the best university in Nigeria was placed in the 30th position. According to the Times Higher Education (2022), the best university in Africa was University of Cape Town in South Africa, which is the 183 rd in the world, with only two Nigerian Universities making it to the top 10 in Africa.…”
Section: Introductionmentioning
confidence: 99%